Positive electrode material and preparation method thereof, positive electrode, battery and electrical equipment
By covering the thin carbon coating layer on the inner core of lithium iron phosphate and doping metal elements, the problems of low electronic conductivity and poor low-temperature electrochemical performance of lithium iron phosphate positive electrode material are solved, high powder compaction density and high battery capacity are achieved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202410454516.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-04-04
AI Technical Summary
As a positive electrode material, lithium iron phosphate has problems such as low electronic conductivity and poor low-temperature electrochemical performance, which limits its high current charging and discharging capabilities and further development of energy storage battery applications.
By covering a thinner carbon coating on the inner core surface of the lithium iron phosphate, combined with doped elements such as magnesium, titanium, vanadium and tin, a positive electrode material with high powder compaction density and high battery capacity was prepared.
The high powder compaction density and high battery capacity of the positive electrode material are achieved, the electronic conductivity and low-temperature electrochemical performance are improved, and the cycle life and service life of the battery are improved.
Smart Images

Figure CN119764359A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode, a battery, and an electrical device. Background Art
[0002] The positive electrode material is the key to determining the performance of the battery, and lithium iron phosphate is widely used as the positive electrode material of energy storage batteries due to its advantages such as low cost, high energy density, stable operating voltage, high theoretical specific capacity, pollution-free, high stability, and long cycle life. It is used in new energy vehicles, energy storage power stations, and special medical equipment. However, due to the particularity of its structure and the influence of polarization phenomena and crystal defects, the diffusion rate of lithium ions in the channel of lithium iron phosphate slows down, which in turn leads to low electronic conductivity and poor low-temperature electrochemical performance. Problems limit its high current charge and discharge capabilities and its further development in energy storage battery applications. At present, lithium iron phosphate is mainly modified by surface coating, ion doping, particle nano-sizing, etc. to overcome the above defects, but the above methods are difficult to simultaneously improve the powder compaction density and battery capacity of the positive electrode material. Summary of the invention
[0003] In view of this, the present application provides a positive electrode material and a preparation method thereof, a positive electrode, a battery and an electrical device. The positive electrode material includes a lithium iron phosphate core and a carbon coating layer. The present application coats the surface of the lithium iron phosphate core with a thin carbon coating layer so that the positive electrode material has both a higher powder compaction density and a higher battery capacity.
[0004] In a first aspect, the present application provides a positive electrode material, which includes a lithium iron phosphate core and a carbon coating layer coated on the surface of the lithium iron phosphate core, wherein the thickness of the carbon coating layer is 0.2nm-0.4nm.
[0005] In the embodiment of the present application, the particle size D50 of the lithium iron phosphate core is 200nm-300nm; the specific surface area of the positive electrode material is 15m 2 / g-20m 2 / g.
[0006] In an embodiment of the present application, the positive electrode material further includes a doping element, and the doping element includes one or more of magnesium, titanium, vanadium and tin. The mass percentage of the doping element in the positive electrode material is 0.05%-4%.
[0007] In the embodiment of the present application, the powder compaction density of the positive electrode material is 2.4 g / cm 3 -2.5g / cm 3 ; and / or, the room temperature discharge specific capacity of the positive electrode material is 155mAh / g-160mAh / g.
[0008] The second aspect of the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0009] Adding an iron source, a lithium source, a phosphorus source, a first carbon source and a second carbon source into deionized water, and mixing them to obtain a positive electrode material precursor slurry;
[0010] Grinding and drying the positive electrode material precursor slurry to obtain a positive electrode material precursor;
[0011] Sintering the cathode material precursor to obtain the cathode material;
[0012] The first carbon source includes polyethylene glycol, and the second carbon source is different from the first carbon source.
[0013] In an embodiment of the present application, the iron source includes one or more of ferric phosphate and ferrous oxalate; the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate and lithium hydroxide; the phosphorus source includes one or more of ferric phosphate, lithium dihydrogen phosphate, phosphoric acid and sodium dihydrogen phosphate; the second carbon source includes one or more of glucose, sucrose, citric acid and starch.
[0014] In an embodiment of the present application, the mass ratio of the iron source, the lithium source, the phosphorus source, the second carbon source and the first carbon source is 1:(0.24-0.25):(1.0-1.11):(0.11-0.12):(0.01-0.03).
[0015] In the embodiment of the present application, the molecular weight of the polyethylene glycol is 200-10000.
[0016] In the embodiment of the present application, the grinding includes dividing the positive electrode material precursor slurry into two slurries for grinding, wherein the particle size D50 of one slurry after grinding is 1.5μm-2.0μm, and the particle size D50 of the other slurry after grinding is 0.2μm-0.5μm.
[0017] In the implementation manner of the present application, the mixing includes stirring operation and shearing treatment performed in sequence; the shearing speed of the shearing treatment is 10000r / min-30000r / min; the grinding includes sand grinding, and the rotation speed of the sand grinding is 1200r / min-2400r / min.
[0018] In the embodiment of the present application, the shearing process further includes adding a doping metal source, and the doping metal source includes one or more of a magnesium source, a titanium source, a vanadium source and a tin source;
[0019] Preferably, the mass of the doping metal source is 1%-5% of the mass of the iron source;
[0020] Preferably, the magnesium source comprises MgCO 3 、MgO、Mg(OH) 2 and MgCl 2 One or more of; and / or, the titanium source comprises TiO 2 、TiCl 4 and Ti(NO 3 ) 4 One or more of; and / or, the vanadium source comprises V 2 O 5 、V 2 O 3 and NaVO 3 One or more of; and / or, the tin source comprises SnCl 4 , SnO and SnSO 4 One or more of .
[0021] The third aspect of the present application provides a positive electrode, including a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material includes the positive electrode material as described in the first aspect or the positive electrode material obtained by the preparation method of the positive electrode material described in the second aspect of the present application.
[0022] A fourth aspect of the present application provides a battery, wherein the battery has a positive electrode as described in the third aspect.
[0023] A fifth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery as described in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the cross-sectional structure of a positive electrode material provided in one embodiment of the present application;
[0025] Figure 2 A flow chart of the method for preparing the positive electrode material provided in this application;
[0026] Figure 3 This is a schematic diagram of the distribution of frosted grain size used in the preparation process of the positive electrode material in one embodiment of the present application;
[0027] Figure 4 Transmission Electron Microscope (TEM) characterization photos of the positive electrode materials of Example 1 and Comparative Example 1;
[0028] Figure 5 This is a scanning electron microscope (SEM) characterization photograph of the positive electrode material of Comparative Example 1;
[0029] Figure 6This is a SEM characterization photograph of the positive electrode material of Example 1;
[0030] Figure 7 This is a SEM characterization photograph of the positive electrode material of Example 6;
[0031] Figure 8 The electrochemical impedance spectra of the positive electrode materials of Example 1 and Comparative Example 1 are shown.
[0032] Description of Figure Numbers
[0033] 100-positive electrode material; 101-carbon coating layer; 102-lithium iron phosphate core. DETAILED DESCRIPTION
[0034] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0035] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0036] The positive electrode material is the key to determining the performance of the battery, and lithium iron phosphate is widely used as the positive electrode material of energy storage batteries due to its advantages such as low cost, high energy density, stable operating voltage, high theoretical specific capacity, pollution-free, high stability, and long cycle life. It is used in new energy vehicles, energy storage power stations, and special medical equipment. However, due to the particularity of its structure and the influence of polarization phenomena and crystal defects, the diffusion rate of lithium ions in the channel of lithium iron phosphate slows down, which in turn leads to low electronic conductivity and poor low-temperature electrochemical performance. Problems limit its high current charge and discharge capabilities and its further development in energy storage battery applications. At present, lithium iron phosphate is mainly modified by surface coating, ion doping, particle nano-sizing, etc. to overcome the above defects, but the above methods are difficult to simultaneously improve the powder compaction density and battery capacity of the positive electrode material.
[0037] In response to the above problems, the present application provides a positive electrode material, which includes a lithium iron phosphate core and a carbon coating layer. The present application coats the surface of the lithium iron phosphate core with a thin carbon coating layer so that the positive electrode material has both a higher powder compaction density and a higher battery capacity.
[0038] See also Figure 1, the present application provides a positive electrode material 100, the positive electrode material 100 includes a lithium iron phosphate core 102 and a carbon coating layer 101 coated on the surface of the lithium iron phosphate core 102, and the thickness of the carbon coating layer 101 is 0.2nm-0.4nm. In some specific embodiments of the present application, the thickness of the carbon coating layer 101 can be, for example, 0.2nm, 0.21nm, 0.22nm, 0.23nm, 0.25nm, 0.26nm, 0.28nm, 0.3nm, 0.32nm, 0.35nm, 0.38nm, 0.4nm. The positive electrode material 100 of the present application controls the thickness of the carbon coating layer 101 within a suitable thinner range, which can significantly improve the powder compaction density of the positive electrode material while ensuring that the positive electrode material maintains good conductivity, thereby obtaining a positive electrode material with both good electrochemical properties and high powder compaction density. In the embodiment of the present application, the lithium iron phosphate core may be modified or unmodified lithium iron phosphate, and the modification method includes but is not limited to element doping modification.
[0039] In the embodiment of the present application, the particle size D50 of the lithium iron phosphate core 102 is 200nm-300nm. In some embodiments of the present application, the particle size D50 of the lithium iron phosphate core 102 can be, for example, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm. The present application controls the particle size of the lithium iron phosphate core 102 within the above range, and cooperates with the thickness of the carbon coating layer 101. While ensuring that the lithium iron phosphate core provides a higher capacity and rate performance for the positive electrode material, it can also avoid the reduction of the positive electrode material powder compaction density caused by the excessive thickness of the carbon coating layer, thereby increasing the internal resistance and polarization of the battery, and obtaining a positive electrode material with both a higher capacity and a higher powder compaction density.
[0040] In the embodiment of the present application, the specific surface area of the positive electrode material 100 is 15 cm 2 / g-20cm 2 In some embodiments of the present application, the specific surface area of the positive electrode material 100 may be, for example, 15 cm 2 / g, 16cm 2 / g, 17cm 2 / g, 18cm 2 / g, 19cm 2 / g, 20cm 2 / g. The specific surface area of the positive electrode material 100 is controlled at 15cm 2 / g-20cm 2 / g is within a smaller range, the powder compaction density and room temperature capacity of the positive electrode material 100 can be further improved. In some embodiments of the present application, the porosity of the carbon coating layer is 5%-10%. In some embodiments of the present application, the porosity of the carbon coating layer can be, for example, 5%, 6%, 7%, 8%, 9%, 10%. By controlling the porosity of the carbon coating layer within the above range, a denser carbon coating layer 101 can be obtained while ensuring better electrochemical properties of the positive electrode material. On the one hand, a denser carbon coating layer can be more closely combined with the lithium iron phosphate core 102, and on the other hand, it can also significantly improve the powder compaction density of the positive electrode material 100, reduce internal resistance, extend the cycle performance of the battery, and improve the service life of the battery.
[0041] In some embodiments of the present application, the positive electrode material 100 further includes a doping element, and the doping element includes one or more of magnesium, titanium, vanadium and tin. In an embodiment of the present application, the mass percentage of the doping element in the positive electrode material 100 is 0.05%-4%. In some embodiments of the present application, the mass percentage of the doping element in the positive electrode material 100 includes but is not limited to 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%. By adding doping metal sources such as magnesium, titanium, vanadium, and tin during the preparation of the positive electrode material and controlling the added amount within an appropriate range, the dispersibility of the positive electrode material 100 and the morphology of the positive electrode material 100 can be effectively improved, so that the positive electrode material 100 is dispersed more evenly, the particle size is more uniform, and the particle morphology is more rounded. At the same time, the particle size is further reduced, providing a shorter diffusion path for lithium ions, improving the diffusion coefficient of lithium ions, and thereby increasing conductivity, reducing resistance and polarization, and improving its cycle life and comprehensive electrochemical performance.
[0042] In the embodiment of the present application, the powder compaction density of the positive electrode material 100 is 2.4 g / cm 3 -2.5g / cm 3 In some specific embodiments of the present application, the powder compaction density of the positive electrode material 100 may be, for example, 2.4 g / cm 3 , 2.41g / cm 3 , 2.42g / cm 3 , 2.43g / cm 3 , 2.44g / cm 3 , 2.45g / cm 3 , 2.46g / cm 3 , 2.47g / cm 3 , 2.48g / cm 3 , 2.49g / cm3 , 2.5g / cm 3 The powder compaction density test method is: using a powder compaction density tester, after the air compression is completed, the positive electrode material sample is placed in the mold, and then placed in the groove, the powder compaction density test scheme is selected and the sample mass is input for compaction density test to obtain the powder compaction density of the positive electrode material.
[0043] In the embodiment of the present application, the room temperature discharge specific capacity of the positive electrode material 100 is 155mAh / g-160mAh / g. When the room temperature discharge specific capacity is tested in the present application, a metal lithium sheet is selected as the negative electrode, and the electrolyte is 1mol / L LiPF 6 A solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1 is assembled into a battery with a positive electrode sheet made from the positive electrode material 100, and its room temperature discharge specific capacity is tested. In some specific embodiments of the present application, the room temperature discharge specific capacity of the positive electrode material 100 can be, for example, 155mAh / g, 156mAh / g, 157mAh / g, 158mAh / g, 159mAh / g, and 160mAh / g. The present application obtains a positive electrode material 100 having both a higher powder compaction density and a higher battery capacity by obtaining a thinner carbon coating layer 101.
[0044] The positive electrode material provided in the present application is obtained by coating a thin carbon coating layer on the surface of the lithium iron phosphate core to obtain a carbon coating layer with high density, low specific surface area and thin thickness, thereby increasing the powder compaction density of the positive electrode material and effectively improving the dispersibility and product consistency of the positive electrode material, thereby reducing the internal resistance of the battery and reducing polarization, and obtaining a positive electrode material with both high powder compaction density and high battery capacity.
[0045] See also Figure 2 , Figure 2 The flowchart of the method for preparing the positive electrode material provided in the present application. The method for preparing the positive electrode material provided in the present application comprises the following steps:
[0046] S101, adding an iron source, a lithium source, a phosphorus source, a first carbon source and a second carbon source into deionized water, and mixing them to obtain a positive electrode material precursor slurry;
[0047] S102, grinding and drying the positive electrode material precursor slurry to obtain a positive electrode material precursor;
[0048] S103, sintering the positive electrode material precursor to obtain a positive electrode material.
[0049] In step S101, the first carbon source includes polyethylene glycol, and the second carbon source is different from the first carbon source. The carbon source in the raw material for preparing the positive electrode material of the present application includes a first carbon source polyethylene glycol and a second carbon source of a commonly used carbon source. Compared with the iron source, lithium source, and traditional carbon source of the conventional carbon-coated lithium iron phosphate positive electrode material, the present application uses polyethylene glycol to replace part of the traditional carbon source to prepare the carbon coating layer. Compared with the traditional carbon source, the polyethylene glycol of the present application has higher stability and connection performance. The carbon coating layer 101 on the surface of the positive electrode material 100 obtained by using it to replace part of the traditional carbon source as a raw material is more uniform and dense, thinner, and smaller in specific surface area, thereby improving the powder compaction density and room temperature capacity of the positive electrode material 100. In addition, polyethylene glycol also has good chemical adsorption capacity and surface tension, which can effectively prevent the aggregation of positive electrode material particles, effectively improve the dispersion uniformity and stability of the positive electrode material, and is more conducive to improving the lithium ion diffusion coefficient, thereby further improving the powder compaction density and electrochemical performance of the positive electrode material.
[0050] In the embodiments of the present application, the molecular weight of polyethylene glycol is 200-10000. In some embodiments of the present application, polyethylene glycol includes but is not limited to one or more of polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800, polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 6000 and polyethylene glycol 10000. In some embodiments of the present application, polyethylene glycol is polyethylene glycol 4000. On the one hand, polyethylene glycol 4000 has a wide range of sources and a relatively low cost. On the other hand, polyethylene glycol 4000 has a relatively low molecular weight and has good dispersibility. Compared with carbon sources such as glucose, the residual carbon rate is low, and a positive electrode material with a low specific surface area and relatively dispersed particles can be formed.
[0051] In the embodiment of the present application, the iron source includes one or more of ferric phosphate and ferrous oxalate; the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate and lithium hydroxide; the phosphorus source includes one or more of ferric phosphate, lithium dihydrogen phosphate, phosphoric acid and sodium dihydrogen phosphate; the second carbon source includes one or more of glucose, sucrose, citric acid and starch. In some embodiments of the present application, ferric phosphate can be used as the iron source of the lithium iron phosphate kernel 102, or as the phosphorus source of the lithium iron phosphate kernel 102; lithium dihydrogen phosphate can be used as the lithium source of the lithium iron phosphate kernel 102, or as the phosphorus source of the lithium iron phosphate kernel 102. The carbon source in the present application includes one or more of glucose, sucrose, citric acid and starch. The carbon coating layer 101 formed by the above-mentioned second carbon source is relatively loose and has a large specific surface area. The present application uses part of polyethylene glycol to replace the above-mentioned second carbon source, thereby effectively improving the density of the carbon coating layer 101 and reducing its specific surface area, thereby significantly improving the powder compaction density and battery capacity of the positive electrode material.
[0052] In an embodiment of the present application, the mass ratio of the iron source, the lithium source, the phosphorus source, the second carbon source and the first carbon source is 1:(0.24-0.25):(1.0-1.11):(0.11-0.12):(0.01-0.03). In some specific embodiments of the present application, the mass ratio of the iron source, the lithium source, the phosphorus source, the second carbon source and the first carbon source can be, for example, 1:0.24:1:0.11:0.01, 1:0.25:1:0.11:0.01, 1:0.24:1.05:0.11:0.01, 1:0.24:1.11:0.11:0.01, 1:0.24:1:0.12:0.01, 1:0.24:1:0.11:0.02, 1:0.24:1:0.11:0.03. In view of the high capacity performance of lithium iron phosphate and the important role of the dense carbon coating layer in improving the compaction density of the material powder, the application controls the mass ratio of the iron source, lithium source, phosphorus source, second carbon source and first carbon source within the above range in consideration of the cooperation between the lithium iron phosphate core 102 and the carbon coating layer 101. By controlling the total mass of the carbon source within the range of 12%-15% of the mass of the iron source, the thickness of the carbon coating layer 101 can be effectively controlled within a suitable range, effectively avoiding problems such as low conductivity of the positive electrode material caused by poor carbon coating modification due to a thin carbon layer and reduced capacity of the positive electrode material caused by the relatively small mass of lithium iron phosphate due to a thick carbon layer. In addition, by reasonably setting the ratio of the second carbon source to the first carbon source within the range of (0.11-0.12):(0.01-0.03), compared with not adding polyethylene glycol or fully utilizing polyethylene glycol as the carbon source, the present application controls the replacement amount of the carbon source with polyethylene glycol within an appropriate range, and obtains a carbon coating layer with high density, low specific surface area and thin thickness on the basis of effectively controlling the cost, thereby increasing the powder compaction density of the positive electrode material and effectively improving the dispersibility and product consistency of the positive electrode material, thereby reducing the internal resistance of the battery and reducing polarization, and obtaining a positive electrode material with excellent electrochemical properties.
[0053] In some embodiments of the present application, grinding can be to divide the positive electrode material precursor slurry into two slurries for grinding, wherein one slurry is ground to a particle size D50 of 1.5μm-2.0μm, and the other slurry is ground to a particle size D50 of 0.2μm-0.5μm, and then the two slurries with different particle sizes are mixed. In some specific embodiments of the present application, the mass ratio of the slurry with a particle size D50 of 1.5μm-2.0μm and the slurry with a particle size D50 of 0.2μm-0.5μm can be 1:1, for example. During grinding, the slurry is divided into two parts with different particle sizes D50 for grinding and the particle size and ratio are controlled within the above range to achieve the particle size matching of the slurry.
[0054] In some embodiments of the present application, the mixing method includes stirring operation and shearing treatment performed in sequence; the shearing speed of the shearing treatment is 10000r / min-30000r / min. In some specific embodiments, the shearing speed of the shearing treatment can be, for example, 10000r / min, 15000r / min, 20000r / min, 25000r / min, 30000r / min. By shearing treatment and controlling the parameters of the shearing treatment within a suitable range, the solidified iron source, lithium source, carbon source and polyethylene glycol raw materials after stirring and mixing can be mixed and dispersed more evenly, and a positive electrode material precursor with relatively uniform raw material components per unit volume can be obtained. In addition, the shearing treatment can also reduce the size of the positive electrode material precursor slurry accordingly, which is beneficial to subsequent sanding and other processing processes.
[0055] In step S102, the grinding method includes sand milling, and the speed of sand milling is 1200r / min-2400r / min. In some specific embodiments, the speed of sand milling can be, for example, 1200r / min, 1300r / min, 1400r / min, 1500r / min, 1600r / min, 1800r / min, 2000r / min, 2200r / min, 2400r / min. In some embodiments of the present application, the specific operation of sand milling can be, for example, when the sealed pump and the main engine are in the starting state, slowly pouring the sheared slurry into the sand mill, rinsing the slurry remaining in the beaker, and pouring it into the sand mill. The sand milling process can effectively reduce the size of the positive electrode material precursor and improve its uniformity, thereby improving the performance uniformity of the final positive electrode material.
[0056] In some embodiments of the present application, the drying method may be spray drying, for example. In some specific embodiments, the specific operation of spray drying may be, for example: inserting the feed pipe into the rotating slurry, when the inlet temperature is stably maintained at 100°C, turning on the feed switch, and performing spray drying at a feed speed of about 60r / min. Compared with other drying methods, the use of spray drying can make the formed powder more uniform in performance, and this method has a shorter drying time and higher efficiency, which is conducive to subsequent process operations.
[0057] In step S103, the protective atmosphere during sintering includes but is not limited to nitrogen. In the embodiment of the present application, the sintering temperature is 700°C-800°C, and the sintering holding time is 7h-9h. In some specific embodiments of the present application, the sintering temperature can be, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, and the sintering holding time can be, for example, 7h, 7.5h, 8h, 8.5h, 9h. In some embodiments of the present application, the heating rate of sintering can be, for example, 5°C / min. By controlling the calcination conditions within the above range, the present application can fully sinter the cathode material precursor to obtain a cathode material with better morphology and more uniform distribution, thereby increasing the powder compaction density of the cathode material and improving its electrochemical performance.
[0058] In some embodiments of the present application, the shearing process further includes adding a doping metal source. In some embodiments of the present application, the doping metal source includes one or more of a magnesium source, a titanium source, a vanadium source, and a tin source. In some embodiments of the present application, the magnesium source includes MgCO 3 、MgO、Mg(OH) 2 and MgCl 2 One or more of; and / or, the titanium source comprises TiO 2 、TiCl 4 and Ti(NO 3 ) 4 One or more of; and / or, the vanadium source comprises V 2 O 5 、V 2 O 3 and NaVO 3 One or more of; and / or, the tin source comprises SnCl 4 , SnO and SnSO 4 One or more of .
[0059] In the implementation manner of the present application, the mass of the doped metal source is 1%-5% of the mass of the iron source. In some specific implementation manners of the present application, the mass of the doped metal source can be, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of the mass of the iron source. The method of adding the doped metal source in the present application can be to slowly add it during the shearing treatment after stirring the slurry. The present application can effectively make the obtained positive electrode material more evenly dispersed, the size of the positive electrode material particles more uniform, the morphology of the positive electrode material particles more rounded, and further reduce the particle size of the positive electrode material, provide a shorter diffusion path for lithium ions, and improve the diffusion coefficient of lithium ions, thereby increasing conductivity, reducing resistance and polarization, and improving its cycle life and comprehensive electrochemical performance by adding the doped metal source when preparing the positive electrode material precursor slurry and controlling the addition amount within the above-mentioned appropriate range.
[0060] The preparation method provided in the present application has a simple process and low cost. By selecting polyethylene glycol to replace part of the commonly used carbon source as the carbon source, a carbon coating layer with high density, low specific surface area and thin thickness is obtained on the surface of the lithium iron phosphate core. The prepared positive electrode material has good product consistency and stability, good powder compaction density and high capacity, which can effectively reduce battery resistance and polarization, improve the electrochemical performance of the battery, and extend the service life of the battery.
[0061] The present application also provides a positive electrode, which includes a current collector and a positive electrode active material loaded on the current collector, and the positive electrode active material includes the positive electrode material provided above or the positive electrode material prepared by the preparation method described above.
[0062] The present application also provides a battery, which includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the positive electrode includes the positive electrode provided above.
[0063] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0064] The present application is further described below in multiple embodiments:
[0065] Example 1
[0066] 100 g of iron phosphate, 24 g of lithium carbonate, 11 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 h to obtain a positive electrode material.
[0067] Example 2
[0068] 100 g of iron phosphate, 24.5 g of lithium carbonate, 11 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 h to obtain a positive electrode material.
[0069] Example 3
[0070] 100 g of iron phosphate, 25 g of lithium carbonate, 11 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 hours to obtain a positive electrode material.
[0071] Example 4
[0072] 100 g of iron phosphate, 24 g of lithium carbonate, 12 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand milling, and spray dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace with nitrogen introduced, and sintered at 780° C. for 8 h to obtain a positive electrode material.
[0073] Example 5
[0074] 100 g of iron phosphate, 25 g of lithium carbonate, 12 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 h to obtain a positive electrode material.
[0075] Example 6
[0076] 100 g of iron phosphate, 24 g of lithium carbonate, 11 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and 1 g of magnesium carbonate was added and stirred evenly, and then spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace with nitrogen introduced, and sintered at 780° C. for 8 h to obtain a positive electrode material.
[0077] Example 7
[0078] 100 g of ferric phosphate, 24 g of lithium carbonate, 12 g of glucose and 1 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was initially stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was evenly divided into two parts and added to a sand mill for sand grinding, one part was sand ground to a particle size D50 of 0.2 μm-0.5 μm, and the other part was sand ground to a particle size D50 of 1.5 μm-2.0 μm. The specific particle size distribution is as follows: Figure 3 As shown, Figure 3 (a) is the particle size distribution of particle size D50 in the range of 0.2μm-0.5μm, Figure 3 (b) shows the particle size distribution of particle size D50 in the range of 1.5 μm-2.0 μm. The two portions of the sand-milled slurry are uniformly stirred and mixed, and then spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder is placed in a tubular furnace filled with nitrogen and sintered at 780°C for 8 hours to obtain a positive electrode material.
[0079] Example 8
[0080] 100 g of iron phosphate, 24 g of lithium carbonate, 12 g of glucose and 3 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand milling, and spray dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace with nitrogen introduced, and sintered at 780°C for 8 hours to obtain a positive electrode material.
[0081] Comparative Example 1
[0082] 100 g of iron phosphate, 24 g of lithium carbonate and 11 g of glucose were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 hours to obtain a positive electrode material.
[0083] Comparative Example 2
[0084] 100 g of iron phosphate, 25 g of lithium carbonate and 12 g of polyethylene glycol were mixed, 0.8 L of deionized water was added, and the mixture was preliminarily stirred with a stirring rod, and then sheared with a shearing machine to obtain a uniformly mixed slurry; the slurry was added to a sand mill for sand grinding, and spray-dried to obtain a positive electrode material precursor powder; the positive electrode material precursor powder was placed in a tubular furnace filled with nitrogen and sintered at 780° C. for 8 hours to obtain a positive electrode material.
[0085] The positive electrode materials of Example 1 and Comparative Example 1 were characterized by scanning electron microscope (SEM), and the thickness of the carbon coating layer of the positive electrode materials was statistically analyzed. The results are as follows: Figure 4 , Figure 5 and Figure 6 As shown, Figure 4 (a) and Figure 5 For comparative example 1, Figure 4 (b) and Figure 6 This is Example 1. Figure 4 It can be seen that the carbon coating layer of the positive electrode material prepared by adding polyethylene glycol to the raw materials is thinner, with an average thickness of 0.2nm-0.4nm, while the carbon coating layer of the positive electrode material prepared without adding polyethylene glycol is thicker, with an average thickness of 1.0nm-1.5nm. Figure 5 and Figure 6 It can be seen that the positive electrode material obtained by replacing part of the carbon source with polyethylene glycol in the present application has a better morphology distribution, a smaller specific surface area, and a more uniform particle size distribution than the positive electrode material prepared without adding polyethylene glycol.
[0086] The positive electrode materials of Example 1 and Example 6 were characterized by scanning electron microscope (SEM), and the results obtained were as follows: Figure 6 and Figure 7 As shown, Figure 6 For Example 1, Figure 7 This is Example 6. Figure 6 and Figure 7 It can be seen that after adding the magnesium source, the particles of the positive electrode material obtained are smaller, the dispersion and uniformity are better, and the morphology of the particles of the positive electrode material obtained is more rounded.
[0087] Performance Testing
[0088] Take 5 g of the positive electrode material obtained in Examples 1-8 and Comparative Examples 1-2 respectively, dry them at 120°C for more than 5 h, and mix them evenly with 1.0814 g of conductive agent graphene and carbon nanotubes, 1.2964 g of polyvinylidene fluoride (PVDF) and 2.5 g of 1-methyl-2-pyrrolidone (NMP) to form a viscous slurry, apply it on both sides of the aluminum foil, and bake it at 110°C. After 15 minutes, the dried double-sided electrode piece is rolled at a pressure of 10 MPa, and the electrode piece sample is obtained after cutting.
[0089] The cut electrode sample was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the Celgard 2300 microporous membrane was used as the separator, and the electrolyte was 1 mol / L LiPF 6 The cells were prepared by mixing ethylene carbonate (EC) and dimethyl carbonate (DMC) solutions in a volume ratio of 1:1 and then assembled into CR2025 button cells in an argon-filled glove box.
[0090] Powder compaction density test
[0091] Using a powder compaction density tester, after the air compression is completed, the positive electrode material samples of Examples 1-8 and Comparative Examples 1-2 are placed in the mold, and then placed in the groove. The powder compaction density test scheme is selected and the sample mass is input to perform a compaction density test to obtain the powder compaction density of the positive electrode material. The results are shown in Table 1.
[0092] Capacity test
[0093] The button cells made of the positive electrode materials of Examples 1-8 and Comparative Examples 1-2 were subjected to constant current charge and discharge tests using the Xinwei 3008 battery test system. The battery to be tested was placed in the middle of the battery cabinet channel fixture, and the test software was opened according to the following steps: (1) Stand for 5 minutes; (2) Constant current charging, current 0.80 mA, cut-off voltage 3.8 V; (3) Constant voltage charging, cut-off current 0.10 mA, voltage 3.8 V; (4) Stand for 5 minutes; (5) Constant current discharge, current 0.80 mA, cut-off voltage 2.5 V. After the battery startup test, the blue data display of the test cabinet channel appears on the interface, and the red light on the test cabinet indicates the room temperature discharge specific capacity. The measured results are shown in Table 1.
[0094] Electrochemical Impedance Spectroscopy (EIS) Test
[0095] The button cells made of the positive electrode materials of Examples 1-8 and Comparative Examples 1-2 were placed in the middle of the aisle of the battery cabinet, and the current values at the rates of 0.1C, 0.5C, 1C, 2C, and 5C were calculated according to the mass of the electrode pieces. The test software was opened and the following steps were followed: (1) Stand for 5 min; (2) Constant current charging at 3.8 V, 0.1 C current; (3) Constant voltage charging at 3.8 V, cut-off current 0.01 C; (4) Stand for 5 min; (5) Constant current discharge to 2.5 V, 0.1 C current; Steps (1) to (5) were repeated 5 times, each with a different discharge current value. Each time, the current values of 0.1C, 0.5C, 1C, 2C, and 5C were input in step (1), and the other steps were the same. The battery after the above cycle was subjected to electrochemical impedance spectroscopy (EIS) test at a frequency of 0.05 Hz on an electrochemical workstation. The measured results are shown in Table 1, where the relevant test results of Example 1 and Comparative Example 1 are shown in Table 1. Figure 8 shown.
[0096] Carbon coating thickness test
[0097] The samples prepared in Examples 1-8 and Comparative Examples 1-2 were imaged by transmission electron microscopy, and the thickness of the carbon coating layer was measured and calculated from the obtained images. The measured results are shown in Table 1.
[0098] Specific surface area test
[0099] The cathode material samples prepared in the embodiments and comparative examples were subjected to desorption gas treatment at low temperature to remove moisture, gas and other impurities adsorbed on the surface, and the samples were measured using a specific surface area analyzer (gas adsorption method). According to the measured data, the calculation formula was: S = L × Vm × Am, where L is the Avogadro constant, Am is the area occupied by each molecule in the unit molecular layer, and Vm is calculated based on a certain adsorption isotherm that conforms to the experimental isotherm. The adsorption amount required to cover the sample surface with a single layer of molecules is calculated. The specific surface area of the sample is calculated, and the measured results are shown in Table 1.
[0100] Table 1 Structure and related performance test results of Examples 1-8 and Comparative Examples 1-2
[0101]
[0102] It can be seen from the data of Examples 1-8 and Comparative Examples 1-2 in Table 1 that the thickness of the carbon coating layer of the positive electrode material prepared by Examples 1-8 provided in the present application is in the range of 0.2nm-0.4nm, while the thickness of the carbon coating layer prepared by Comparative Example 1 using glucose as the carbon source and Comparative Example 2 using polyethylene glycol as the carbon source is 1nm. Compared with the carbon coating layer of the positive electrode material of Comparative Examples 1 and 2, the thickness of the carbon coating layer of the positive electrode material prepared by using polyethylene glycol to replace part of the traditional carbon source in the present application embodiment is significantly reduced, the specific surface area is reduced, and the powder compaction density of the positive electrode material is increased. The room temperature discharge specific capacity and lithium ion diffusion coefficient of the battery prepared using the positive electrode material of the present application embodiment are improved, the resistance is reduced, and it has excellent electrochemical properties.
[0103] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a lithium iron phosphate core and a carbon coating layer coated on the surface of the lithium iron phosphate core, and the thickness of the carbon coating layer is 0.2nm-0.4nm.
2. The positive electrode material according to claim 1, characterized in that The particle size D50 of the lithium iron phosphate core is 200nm-300nm; the specific surface area of the positive electrode material is 15m 2 / g-20m 2 / g.
3. The positive electrode material according to any one of claims 1 or 2, characterized in that The positive electrode material further includes a doping element, which includes one or more of magnesium, titanium, vanadium and tin. The mass percentage of the doping element in the positive electrode material is 0.05%-4%.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The powder compaction density of the positive electrode material is 2.4 g / cm 3 -2.5g / cm 3 ; and / or, the room temperature discharge specific capacity of the positive electrode material is 155mAh / g-160mAh / g.
5. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Adding an iron source, a lithium source, a phosphorus source, a first carbon source and a second carbon source into deionized water, and mixing them to obtain a positive electrode material precursor slurry; Grinding and drying the positive electrode material precursor slurry to obtain a positive electrode material precursor; Sintering the cathode material precursor to obtain the cathode material; The first carbon source includes polyethylene glycol, and the second carbon source is different from the first carbon source.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The iron source includes one or more of ferric phosphate and ferrous oxalate; the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate and lithium hydroxide; the phosphorus source includes one or more of ferric phosphate, lithium dihydrogen phosphate, phosphoric acid and sodium dihydrogen phosphate; the second carbon source includes one or more of glucose, sucrose, citric acid and starch.
7. The method for preparing the positive electrode material according to claim 5 or 6, characterized in that: The mass ratio of the iron source, the lithium source, the phosphorus source, the second carbon source and the first carbon source is 1:(0.24-0.25):(1.0-1.11):(0.11-0.12):(0.01-0.03).
8. The method for preparing a positive electrode material according to any one of claims 5 to 7, characterized in that: The molecular weight of the polyethylene glycol is 200-10000.
9. The method for preparing a positive electrode material according to any one of claims 5 to 8, characterized in that: The grinding includes dividing the positive electrode material precursor slurry into two slurries for grinding, wherein the particle size D50 of one slurry after grinding is 1.5 μm-2.0 μm, and the particle size D50 of the other slurry after grinding is 0.2 μm-0.5 μm.
10. The method for preparing a positive electrode material according to any one of claims 5 to 9, characterized in that: The mixing includes stirring operation and shearing treatment performed in sequence; the shearing speed of the shearing treatment is 10000r / min-30000r / min; the grinding includes sand grinding, and the rotation speed of the sand grinding is 1200r / min-2400r / min.
11. The method for preparing the positive electrode material according to claim 10, characterized in that: The shearing process also includes adding a doping metal source, wherein the doping metal source includes one or more of a magnesium source, a titanium source, a vanadium source and a tin source; Preferably, the mass of the doping metal source is 1%-5% of the mass of the iron source; Preferably, the magnesium source includes one or more of MgCO3, MgO, Mg(OH)2 and MgCl2; and / or, the titanium source includes one or more of TiO2, TiCl4 and Ti(NO3)4; and / or, the vanadium source includes one or more of V2O5, V2O3 and NaVO3; and / or, the tin source includes one or more of SnCl4, SnO and SnSO4.
12. A positive electrode, characterized in that: It comprises a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material comprises the positive electrode material according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method of the positive electrode material according to any one of claims 5 to 11.
13. A battery, characterized in that: The battery comprises the positive electrode as claimed in claim 12.
14. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 13.